Metal Concentrations in Soil Paste Extracts as Affected by Extraction Ratio. (2002) - Tack, Filip M.G.; Dezillie, Nic; Verloo, Marc G.
Abstract : Saturated paste extracts are sometimes used to estimate metal levels in the soil solution. To assess the significance of heavy-metal concentrations measured in saturation extracts, soil paste extracts were prepared with distilled water in amounts ranging from 60–200% of the moisture content at saturation. Trace metals behaved as if a small pool consistently was dissolved independent of the extraction ratio applied. Metal concentrations in the solution hence were not buffered by the solid phase, but the observed behaviour would allow the estimation of metal concentrations in the soil solution as a function of moisture content. The behaviour of iron and manganese suggested that some microbial reduction occurred. The intensity increased with increasing extraction ratio but not to the extent of affecting dissolution of trace elements.